A Literature Review of the Relationship between State-Owned Enterprises and Political Power in a Neo patrimonial Economy - Eka Nur Yulianti (Economic and Business Horizon, 2026)
This article examines corporatocracy, a phenomenon where political and corporate power are intertwined in the Indonesian context, specifically the interrelationship between State-Owned Enterprises and political power within a neopatrimonial economic framework. Using a qualitative systematic literature review approach, this study examines the current literature on State-Owned Enterprises corruption. The analysis reveals that State-Owned Enterprises in Indonesia often serve as fertile ground for structural corruption. For example, public investment funds are often diverted to private pockets, while procurement mechanisms for goods and services are rife with bribery and nepotism. A closed bureaucratic culture that prioritizes patron-client relationships exacerbates this situation. The study compares various findings and confirms that the flow of bribery and collusion within SOEs leads to economic inefficiency and a loss of public trust. The implications of these findings highlight the need to strengthen oversight mechanisms, transparency, and institutional reform of State-Owned Enterprises. Recommendations for further research include empirical case studies on specific corporatocracies (e.g., in the energy or state finance sectors) and analyses of the effects of new State-Owned Enterprises policies to measure the effectiveness of corruption prevention measures at the structural level